(untitled) (South East Asia Journal of Public Health, 2013)
To address poor utilization of maternal and child health services by the rural community, the National Rural Health Mission (NRHM) was launched in 2005 in India. Under NRHM, ASHA (Accredited Social Health Activist) was identified as an effective link between the government and poor pregnant women. The aim of the present study was to examine the utilization of ASHA services under NRHM in relation to maternal health by the Recently Delivered Women (RDW) in the study area. A cross-sectional study was conducted at PHC Sarojini Nagar, Lucknow and its rural field areas. A sample of 350 RDW, chosen by simple random sampling, were interviewed at bedside by a preformed schedule and then were followed up after six weeks. Antenatal registration was reported by 97% RDW of which 73% registered early. About 53% RDW had three or more antenatal care visits. Two dose Tetanus Toxoid coverage was 92.9%. Receipt and consumption of iron and folic acid was low. ASHA was the major facilitator for higher utilization of antenatal care services, except for Iron and Folic Acid receipt/consumption. Low utilization of postnatal care (21.5% RDW had at least one postnatal check-up) is a matter of concern. Knowledge and awareness of ASHA on importance of postnatal care needs to be enhanced via hands on training by specialists and regular orientation programs. Better and intense advocacy in the community regarding importance of availing services of ASHA in relation to maternal health needs to be addressed. South East Asia J Public Health | Jan-June 2012 | Vol 2 Issue 1 | 24-27 DOI: http://dx.doi.org/10.3329/seajph.v2i1.15261